Can simulation models help design rice cultivars that are more competitive against weeds? - Bastiaans, L.; Kropff, M.J.; Kempuchetty, N.; Rajan, A.; Migo, T.R. (Elsevier, 1997)
Differences in competitive ability between rice cultivars IR8 and Mahsuri, grown in well-fertilised irrigated conditions, were analysed by means of a mechanistic simulation model (INTERCOM) for crop-weed interaction. The analysis revealed that the greater competitive ability of Mahsuri was due mainly to a greater relative leaf area growth rate early in the season and larger maximum plant height. Comparison of experimental results and model outcomes indicated, however, that the present model is not entirely able to quantify the trade-off between competitive and yielding ability. The extent to which traits advantageous for competition may lead to increased lodging or a larger number of unproductive tillers is not quantified by the present model. This implies that use of INTERCOM for design of more competitive rice cultivars will require continuous interaction between modelling and experimentation. With those limitations in mind, the model was used to quantify the potential contribution of various attributes to competitive ability. A sensitivity analysis demonstrated that competition for light is mainly determined by morphological characteristics of which early relative leaf area growth rate, early relative height growth rate and maximum plant height were found to be the most important. The ability of the model to identify key traits with respect to competitive ability makes it a useful tool for designing rice ideotypes.